Effect of repeated oral administration of chondroitin sulfate on neuropathic pain induced by partial sciatic nerve ligation in mice - Wataru Nemoto; Kotaro Yamada; Osamu Nakagawasai; Yoshiki Ogata; Masato Chiba; Ryota Yamagata; Hidetomo Sakurai; Koichi Tan-No (Elsevier, 2018)
We examined whether chondroitin sulfate (CS), a compound used to treat osteoarthritis and joint pain, is effective against partial sciatic nerve ligation (PSNL)-induced neuropathic pain. Repeated oral administration of CS (300 mg/kg, b.i.d. for 20 days) resulted in inhibition of tactile allodynia observed 21 days after PSNL. On day 21, phosphorylation of spinal p38 mitogen-activated protein kinase (MAPK) was attenuated by CS. CS also inhibited c-Fos upregulation in ipsilateral deep dorsal horn (laminae III-IV) neurons, which receive Aβ-fiber afferent inputs. These findings suggest that CS attenuates PSNL-induced tactile allodynia by inhibiting spinal p38 MAPK phosphorylation and Aβ-fiber activation. Keywords: Chondroitin sulfate, Partial sciatic nerve ligation, Spinal cord